The integral, a vision of its evolution through time II - Ortiz Fernández, Alejandro (2023)
In this part II we intend to give an overview of the different ways in which the idea of integral has evolved over time; in particular the Riemann integral has been the motivation for further research up to the present. We only want to motivate this part of the history of mathematical analysis in our environment with the aim that student and teachers have a guide for more detailed studies and thus contribute to the development of matematics in our region.